Synthesis of nano lead oxide for the application of lead-acid energy storage devices - Wong, Kin Nyap (2017)
Over the past decades, efforts have been emphasized on electric vehicles (EV) as a major solution to reduce carbon emission for greener environment. While one of the core design components of EV is the energy storage device which is to ensure sustainable power supply in the drive train system. However, existing energy storage applied in EV is relatively expensive, so, affordable and feasible energy storage needs to be explored to achieve the objective of fuel economy.